Analysis of Leadership Style, Work Environment, and Motivation of Employee Performance Mediated by Organizational Culture in the Assembly Work of the National Narcotics Agency North Sumatra Province - Nurhalimah Nasution; Yohny Anwar; Sri Rahayu (International Journal of Management, Economic and Accounting, 2024)
Resource management is one of the most important parts of management. Human factors influence employee and management performance. Managing human resources is more often known as performance management. In performance management, there are various kinds of literature that examine performance principles, leadership, work environment, work motivation, and organizational culture. For this reason, this research aims to analyze leadership style on employee performance, analyze the work environment on employee performance, analyze motivation on employee performance, and analyze the influence of leadership style, work environment, and motivation on employee performance in Organizational Culture Mediation at the Provincial BNN Working Unit. This type of research is quantitative descriptive, the research sample is 100 people, and the data is analyzed using the SEM (structural equation modeling) method. Overall, from the results and discussion of the research, it is concluded that there is a positive and significant influence between leadership style on employee performance, as well as the work environment on employee performance which has a positive and significant influence, then motivation variable has a positive and significant influence on employee performance in the BNN Working Unit. North Sumatra Province. However, this is not the case with organizational culture which does not mediate at all on the variables of leadership style, work environment, and motivation on employee performance in the Provincial BNN Working Unit.